A Classification System of Asian Noses for Rhinoplasty - Ng, Chew Lip (Facial Plastic Surgery, 2024)
While Asian noses are generalized as having smaller bones and softer cartilages, thicker skin and soft tissue envelop (SSTE), there exists a diversity of morphology amongst Asian noses. The oversimplification of Asian noses diminishes the validity or generalizability of rhinoplasty research findings and makes comparison of outcomes challenging. A classification system is proposed that reflects the different structures and SSTEs of the nasal subtypes, the techniques required in the management of each of the subtypes, the challenges the surgeon will face intra- and postoperatively, allows for preoperative counselling of expected outcomes, and facilitate valid and fair comparison of study outcomes by comparing like for like. The classification system stratifies noses into four subtypes based on (1) the size and strength of the nasal bone and cartilages, and (2) the thickness of the SSTE. Type I noses have thinner SSTE and stronger structure. Type II noses have thinner SSTE and weaker structure. Type III noses have thicker SSTE and stronger structure. Type IV noses have thicker SSTE and weaker structure. Interrater variability in classifying noses among rhinoplasty surgeons was found to be very high with a kappa coefficient of 0.933 (95% confidence interval: 0.852–1.014; variance 0.013).
Keywords: Asian; rhinoplasty; morphology; nose; classification